Immunization dropout rate and associated factors among children aged 12-35 months in a rural field practice area: a community-based cross-sectional study - Sushil Shinde; Sarita Wadhva; Pragati Rathod; Jyotsna Deshmukh; Swapnil Tembhekar (International Journal Of Community Medicine And Public Health, 2026)
Background: Immunization is one of the most effective public health interventions for preventing vaccine-preventable diseases and reducing under-five morbidity and mortality. Despite improvements in vaccination coverage under the Universal Immunization Programme, some children fail to complete the recommended schedule. Immunization dropout reflects gaps related to caregivers, health services, and accessibility, making its assessment essential for improving complete immunization coverage. Methods: A community-based cross-sectional study was conducted among 400 children aged 12-35 months residing in the selected study area. Participants were selected using multistage random sampling. Data were collected using a pre-tested semi-structured questionnaire and verified using immunization cards wherever available. Dropout rates were calculated using WHO indicators, including BCG-to-Measles/MR and Pentavalent-1-to-Pentavalent-3 dropout rates. Associations were assessed using the Chi-square test, followed by multivariable logistic regression. A p value 5 km from a health facility were significant independent determinants. Conclusions: Strengthening caregiver awareness, defaulter tracking, card retention, institutional deliveries, and accessibility of vaccination services may reduce immunization dropout and improve complete immunization coverage.